Bracing for impact: operational upshots from the National Centre for Infectious Diseases Screening Centre (Singapore) during the COVID‐19 outbreak - Charmaine Malenab Manauis; Marvin Loh; James Kwan; John Chua Mingzhou; Han Jie Teo; David Teng Kuan Peng; Shawn Vasoo Sushilan; Yee Sin Leo; Ang Hou (Journal of the American College of Emergency Physicians Open)
Abstract To combat the ongoing COVID‐19 pandemic, Singapore has adopted a rigorous screening approach that involves aggressive contact tracing, rapid isolation of confirmed or suspect cases, and immediate ring‐fencing of emerging local clusters and hotspots. Our screening centre team has been involved in running Singapore's designated screening centre since the end of January this year. With a well‐defined blueprint and substantial pre‐outbreak preparatory work, initial operations at our screening centre commenced within a day on activation and full operational status was attained in 3 days. As of 8 April 2020, the screening centre had screened more than 14,000 patients. We have adopted a “whole‐of‐hospital” approach, enlisting the help from other departments and subspecialties to augment manpower. Meticulous infrastructure planning to facilitate patient flow and strict measures to prevent nosocomial transmission and occupational exposure were instituted to safeguard both the staff and patients. This paper aims to describe our key takeaways in the course of operations and discuss the challenges encountered.